Energy price dynamics in the U.S. market. Insights from a heterogeneous multi-regime framework - Dias, J. G.; Ramos, S. (Energy, 2014)
Energy is a key input in investment decision making with a well-known effect on economic growth. Inelasticity of energy demand urges an understanding of its price dynamics. This paper makes a joint analysis of the price of oil, natural gas, and electricity in U.S. markets using a multi-regime specification that captures the stylized facts of energy prices. Oil and natural gas returns have similar regime dynamics and are well characterized by a high and low volatility regime. Electricity returns have to be parameterized with more regimes: a low volatility, a price spike, and a mean-reverting regime. The California crisis period stands out as a sole regime with extremely high volatility. Our methodology allows the synchronization among regimes to be studied and we find that electricity prices tend to be synchronized in U.S. wholesale markets, while natural gas returns show synchronization with electricity returns in the low volatility regime.